Bering, J.: The belief instinct: the psychology of souls, destiny, and the meaning of life. New York: W.W. Norton, 2011, 252 páginas. - Bejarano, Teresa (THÉMATA. Revista de Filosofía, 2013)
Reseña del libro de Bering, J.: The belief instinct: the psychology of souls, destiny, and the meaning of life. New York: W.W. Norton, 2011, 252 páginas.